2022
DOI: 10.1111/dth.15322
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of endovenous laser ablation versus ultrasound‐guided foam sclerotherapy for the treatment of venous leg ulcers

Abstract: Endovenous thermal and non-thermal therapeutic approaches have become standard of care for the treatment of venous insufficiency. However, comparative studies on its use in the population of venous leg ulcer patients are scarce. The present study aimed at a comparison of the efficacy of endovenous laser ablation (EVLA) and ultrasound-guided foam sclerotherapy (UGFS) for the treatment of venous leg ulcers (VUs). We retrospectively analyzed patient records of 68 patients with active VUs (C6 of the CEAP-classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In comparison to foam sclerotherapy, numerous studies showed that foam sclerotherapy has a higher recurrence rate compared to EVLA, [15][16][17] so in our case, foam sclerotherapy is not an option that we would choose.…”
Section: Discussionmentioning
confidence: 69%
“…In comparison to foam sclerotherapy, numerous studies showed that foam sclerotherapy has a higher recurrence rate compared to EVLA, [15][16][17] so in our case, foam sclerotherapy is not an option that we would choose.…”
Section: Discussionmentioning
confidence: 69%
“…Another study compared the efficacy of endovenous laser ablation and UGFS for the treatment of VLUs. Rates of ulcer resolution and ulcer healing time after endovenous intervention were comparable between both treatment modalities 13 . Nevertheless, a significantly higher relapse rate was observed in UGFS‐treated patients.…”
Section: Discussionmentioning
confidence: 77%
“…Rates of ulcer resolution and ulcer healing time after endovenous intervention were comparable between both treatment modalities. 13 Nevertheless, a significantly higher relapse rate was observed in UGFS‐treated patients. Therefore, the optimal method for endovenous ablation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of underlying venous reflux can be achieved through various minimally invasive procedures such as FS and endovenous laser (EVLA) and radiofrequency (RFA) ablation or mechanochemical ablation (MOCA); the latter has been reported as a safe and effective technique in treating chronic venous ulcers, appearing to provide comparable results to techniques relying on thermal ablation. 7 Likewise, Weber et al 8 reported in a small study similar rates of venous ulcer resolution and healing time after EVLA and FS but with significantly higher relapse rate in FS-treated patients.…”
Section: Discussionmentioning
confidence: 93%